DEVELOPING THE INNOVATIVE MENTALITY OF SECONDARY SCHOOL STUDENTS - A. P. Usoltsev; T. N. Shamalo (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to fostering the innovative thinking of secondary school students in the light of widespread introduction and development of high-technologies, and growing demand for innovative specialists, particularly in technical and scientific spheres. The research, aimed at finding the ways for fostering the students' innovative thinking, incorporates the definition and analysis of innovative mentality, including its cognitive and instrumental components, and various characteristics such as creative, theoretical, social, constructive, transformative, and pragmatic ones, which constitute a complex structure of innovative thinking. Based on the specified characteristics of innovative thinking, the authors define the main educational tasks for activating the innovative mentality, and demonstrate the ways for their fulfillment in the context of additional education. The authors believe that the above recommendations can reinforce the readiness of the young generation for innovative professional activity in different spheres, and develop their professional self-determination in accordance with the state demands for the advanced economy.span style='font-size:10.0pt;line-height: 115%;font-family:"BookmanOldStyle","serif";mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin;mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;color:black;mso-ansi-language:RU;mso-fareast-language: EN-US;mso-bidi-language:AR-SA'>ии наук педагогического образования, Екатеринбург